Deletion of the GATA Domain of TRPS1 Causes an Absence of Facial Hair and Provides New Insights into the Bone Disorder in Inherited Tricho-Rhino-Phalangeal Syndromes - Malik, Talat H. (American Society for Microbiology, 2002)
GATA transcription factors mediate cell differentiation in diverse tissues, and their dysfunction is associated with certain congenital human disorders. The six classical vertebrate GATA proteins, GATA-1 to GATA-6, are highly homologous, bear two tandem zinc fingers of the C(4) (GATA) type, and activate transcription. TRPS1, the only other vertebrate protein with the GATA motif, is a large, multitype zinc finger protein that harbors a single DNA-binding GATA domain and represses transcription. Monoallelic TRPS1 mutations cause two dominantly inherited human developmental disorders of the hair, face, and digits, tricho-rhino-phalangeal syndrome (TRPS) types I (MIM 190350) and III (MIM 190351); missense GATA domain mutations account for the more severe type III form. Here we report that heterozygous mice with deletions of the TRPS1 GATA domain (TRPS1(+/Δgt)) display facial anomalies that overlap with findings for TRPS, whereas TRPS1(Δgt/Δgt) mice additionally reveal a complete absence of vibrissae. Unexpectedly, TRPS1(Δgt/Δgt) mice die of neonatal respiratory failure resulting from abnormalities of the thoracic spine and ribs. Heterozygotes also develop thoracic kyphoscoliosis with age and reveal structural deficits in cortical and trabecular bones. These findings directly implicate the GATA type zinc finger of TRPS1 in regulation of bone and hair development and suggest that skeletal abnormalities emphasized in descriptions of TRPS are only the extreme manifestations of a generalized bone dysplasia.